Transformation of Da’wah in the Digital Era: Modern Strategies in Optimizing Technology Based Da’wah Management - Al Kahfi; Kholis Ali Mahmudi; Arjuna (Jurnal Dakwah dan Komunikasi, 2024)
The transformation of da'wah in the digital era has become a significant phenomenon in da'wah management. Along with the development of information and communication technology, da'wah methods have undergone fundamental changes from face-to-face interaction to the use of digital platforms such as social media. This study aims to examine the challenges faced by da'wah organizations in implementing technology, as well as to offer solutions based on the development of a more modern and adaptive da'wah strategy to changing times. Through literature studies and empirical analysis, Although the use of digital media offers wider reach and better accessibility, there are problems such as the digital divide, disinformation, and changes in audience preferences that need to be addressed. This study found that technology-based da'wah strategies must be adjusted to the characteristics and needs of the audience to ensure the relevance and effectiveness of da'wah. The results of this study are expected to provide insight for da'wah institutions in optimizing the use of digital technology, as well as developing a more innovative and responsive approach to social dynamics in society. Thus, the transformation of da'wah in the digital era is not only about adopting technology, but also about implementing strategies that are wise and in accordance with Islamic values.